The Concept of State and the Notion of Responsibility to Protect: a Comparative View by Focusing on Foucault's Thoughts - Aramesh Shahbazi (دولت‌پژوهی, 2015)
The discipline of political science has developed many international legal principles, norms, concepts, agreements, and institutions in realm of contemporary international law. One of the key issues regarding the technique and the structure of this evolution is the mutual interrelation between philosophy, law, society and political science. Meanwhile, reassessment and reconsideration of the theories of the philosophers and political thinkers could be an important vehicle to elaborate on the concepts and to provide the logical justifications and legal backgrounds of the phenomena. In this era, the classic form of State in International law as a complicated concept has been always at the center of the debates. The Montevideo convention (1933) has defined the rights and duties of states. It sets out the four criteria for States such as a permanent population; a defined territory; government; and also capacity to enter into relations with the other states. Yet it is believed that these factors originally refer to the legality of the states, while States are often assumed to be legitimized by value judgments of international community as a whole. Likewise, the concept of responsibility to protect, as a controversial occurrence in international environment, especially at the time of international or domestic conflicts, has created various arguments in both aspects of legality and legitimacy. The former refers to some declarations issued by competence international legal organizations such as the United Nations and the latter refers to admiration and acceptance by international community above all, including the States. The purpose of this paper is to securitize the concept of state and the notion of responsibility to protect by taking a look at Foucault’s thought and also to provide a context in which the mutual interrelations of international law and political thoughts could be emphasized.The first chapter of this article answers the questions concerning the importance of Foucault’s idea in international law and the ways his proposals could elaborate some evolutions in this matter, such as modern States and responsibility to protect. Chapter II examines the concepts has already been examined in the practice of international actors especially States. It also considers the legality and legitimacy of both concepts by way of analogy. The final chapter brings together the Foucault’s thought outlined in Chapter I and the International legal facts set out in Chapter II. It also discusses the relevance and the possibility of a context in which law and political thoughts could be closed.The rise of what Foucault calls as bio- power does not lead to eradication of the concept of law or result in ignorance of the concept of state in general. In Foucault’s thought the concept of State in a modern society has been changed. Consequently both legality and legitimacy could be the considered as important factors for modern States. On the other hand, the notion of responsibility to protect is also a new conception. Likewise, the legality and legitimacy of this concept could be found in international legal instruments and also in the practice and the confidence of international actors including States.